Structural Analysis of E-Sports Industrial Association Network Based on Complex Network Theory - Haibin Wang; Hong Huo; Dongdong Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
A clear regional imbalance exists in the e-sports industry in terms of the industry’s contribution to the overall development of the economy. Available research suggests that this imbalance is a result of regional supporting policies, social culture integration and differences among countries. Therefore, to rationalize the overall structural planning for e-sports industrial association network (IAN), this paper probes into the structure of e-sports IAN based on the complex network theory. Firstly, the key factors affecting the development of the e-sports industry are identified, and an evaluation index system (EIS) is established. Secondly, e-sports IAN is analyzed from two angles, namely, the entire network and enterprise node, based on complex network theory. This study uses an experimental design for gathering data from the respondents. Finally, the clustering structure of e-sports IAN is studied based on modularity, and the network is divided into clusters. The results verify the effectiveness of complex network theory in the structural analysis of e-sports IAN. The economic ties between regional e-sports enterprises enhance slightly in the six years. Compared with the density of the national e-sports industrial network, the region has a certain advantage in e-sports industrial development in 2014. The findings of the present study fill the gaps mentioned in the paper and significantly benenfit practioners and stakeholders as well as help in identifying the salient industries and key areas in e-sports IAN.